Chloride channels in myotonia congenita assessed by velocity recovery cycles. Issue 6 (2nd May 2014) - Tan, S. Veronica; Z'Graggen, Werner J; Boërio, DELPHINE; Rayan, Dipa Raja; Norwood, Fiona; Ruddy, Deborah; Howard, R.; Hanna, Michael G.; Bostock, Hugh
ABSTRACT Introduction: Myotonia congenita (MC) is caused by congenital defects in the muscle chloride channel CLC‐1. This study used muscle velocity recovery cycles (MVRCs) to investigate how membrane function is affected. Methods: MVRCs and responses to repetitive stimulation were compared between 18 patients with genetically confirmed MC (13 recessive, 7 dominant) and 30 age‐matched, normal controls. Results: MC patients exhibited increased early supernormality, but this was prevented by treatment with sodium channel blockers. After multiple conditioning stimuli, late supernormality was enhanced in all MC patients, indicating delayed repolarization. These abnormalities were similar between the MC subtypes, but recessive patients showed a greater drop in amplitude during repetitive stimulation. Conclusions: MVRCs indicate that chloride conductance only becomes important when muscle fibers are depolarized. The differential responses to repetitive stimulation suggest that, in dominant MC, the affected chloride channels are activated by strong depolarization, consistent with a positive shift of the CLC‐1 activation curve. Muscle Nerve49: 845–857, 2014